2006
DOI: 10.1007/s10482-006-9081-y
|View full text |Cite
|
Sign up to set email alerts
|

Megaplasmids encode differing combinations of lantibiotics in Streptococcus salivarius

Abstract: Streptococcus salivarius strains commonly produce bacteriocins as putative anti-competitor or signalling molecules. Here we report that bacteriocin production by the oral probiotic strain S. salivarius K12 is encoded by a large (ca. 190 kb) plasmid. Oral cavity transmission of the plasmid from strain K12 to a plasmid-negative variant of this bacterium was demonstrated in two subjects. Tests of additional S. salivarius strains showed large (up to ca. 220 kb) plasmids present in bacteriocin-producing isolates. V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
71
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 33 publications
0
71
0
3
Order By: Relevance
“…S. thermophilus, a nonpathogenic species in the bovis group that is used in the dairy industry (181), contains a set of plasmids harboring heat shock proteins; Streptococcus mutans, a member of the human indigenous flora that is transmitted mostly from mother to child, often carries 5-to 6-kb cryptic plasmids that parallel the evolution of lineages associated with racial cohorts and geographical locations (182). Megaplasmids in the group salivarius coding for different lantibiotics favor their persistence in the oral cavity (183). Conversely, the pyogenic group, which is represented by species of clinical interest such as S. agalactiae and S. pyogenes (also called GAS and GBS, respectively), frequently carry plasmids that code for AbR genes aside from bacteriocins.…”
Section: Streptococcusmentioning
confidence: 99%
“…S. thermophilus, a nonpathogenic species in the bovis group that is used in the dairy industry (181), contains a set of plasmids harboring heat shock proteins; Streptococcus mutans, a member of the human indigenous flora that is transmitted mostly from mother to child, often carries 5-to 6-kb cryptic plasmids that parallel the evolution of lineages associated with racial cohorts and geographical locations (182). Megaplasmids in the group salivarius coding for different lantibiotics favor their persistence in the oral cavity (183). Conversely, the pyogenic group, which is represented by species of clinical interest such as S. agalactiae and S. pyogenes (also called GAS and GBS, respectively), frequently carry plasmids that code for AbR genes aside from bacteriocins.…”
Section: Streptococcusmentioning
confidence: 99%
“…There is increasing evidence to suggest that bacteriocin production is a desirable probiotic trait that enables the establishment and persistence of the producing strains within the gastrointestinal tract (GIT) (2,9,15,35). These antimicrobials may have a narrow or broad spectrum of inhibition (16).…”
mentioning
confidence: 99%
“…Although the transfer-associated genes within the conjugative megaplasmid pMP118 appear nonfunctional in L. salivarius UCC118 (10), corresponding RepA-type megaplasmids are universally present in L. salivarius (17). Interestingly, Wescombe et al demonstrated the in vivo conjugative transmission of bacteriocin-rich megaplasmids in Streptococcus salivarius species, which was associated with the numerical prominence of the species within the oral cavity (35).…”
mentioning
confidence: 99%
“…This anti-MS activity appears, at least in part, attributable to the production of SalE, a newly described 3565.9 Da class II lantibiotic bacteriocin. The genetic locus specifying the biosynthesis of SalE is located on the 220 kb megaplasmid pSsal-JH, previously shown to also harbour the loci for the bacteriocins salivaricin A3, SA-FF22 and streptin (Wescombe et al, 2006a).…”
Section: Discussionmentioning
confidence: 99%